Long-Term Efficacy of Physical Therapy for Localized Provoked Vulvodynia - Jahshan-Doukhy O; Bornstein J (Dove Medical Press, 2021)
Ola Jahshan-Doukhy,1 Jacob Bornstein2 1Azrieli Faculty of Medicine, Bar-Ilan University, Safed, Israel; 2Department of Obstetrics and Gynecology, Galilee Medical Center, Nahariya, IsraelCorrespondence: Jacob Bornstein Email mdjacob@gmail.comPurpose: The origin of provoked vulvodynia (PV), the main cause of entry dyspareunia, remains unclear, and the treatment is empiric. In this study, we aimed to investigate the long-term effects of physical therapy on PV in subjects using questionnaire concerning PV symptoms immediately after physical therapy and at least 10 years later.Patients and Methods: This study included a total of 24 women diagnosed with PV and referred by their primary physicians to Maccabi Physical Therapy Clinic for pelvic floor rehabilitation between 2004 and 2008. Criteria such as pain relief, sexual functioning, and treatment satisfaction were assessed.Results: The average pain scores of the 24 participants reduced significantly after therapy, and 42% had no pain between treatment and the time of survey. Eighty-three percent did not undergo additional treatment after the initial physical therapy and reported high or very extremely high levels of pain reduction following treatment. Multiple regression analysis found that onset type of PV and age were not associated with the treatment outcome (p = 1.0).Conclusion: Physical therapy is an effective long-term treatment for primary or secondary PV, resulting in pain reduction and improved sexual function.Keywords: dyspareunia, pain management, vulvodynia, physical therapy, vestibulodynia